Enhanced Hippocampal Long-Term Potentiation and Spatial Learning in Aged 11β-Hydroxysteroid Dehydrogenase Type 1 Knock-Out Mice - Yau, Joyce L. W. (J Neurosci, 2007)
Glucocorticoids are pivotal in the maintenance of memory and cognitive functions as well as other essential physiological processes including energy metabolism, stress responses, and cell proliferation. Normal aging in both rodents and humans is often characterized by elevated glucocorticoid levels that correlate with hippocampus-dependent memory impairments. 11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) amplifies local intracellular (“intracrine”) glucocorticoid action; in the brain it is highly expressed in the hippocampus. We investigated whether the impact of 11β-HSD1 deficiency in knock-out mice (congenic on C57BL/6J strain) on cognitive function with aging reflects direct CNS or indirect effects of altered peripheral insulin-glucose metabolism. Spatial learning and memory was enhanced in 12 month “middle-aged” and 24 month “aged” 11β-HSD1(−/−) mice compared with age-matched congenic controls. These effects were not caused by alterations in other cognitive (working memory in a spontaneous alternation task) or affective domains (anxiety-related behaviors), to changes in plasma corticosterone or glucose levels, or to altered age-related pathologies in 11β-HSD1(−/−) mice. Young 11β-HSD1(−/−) mice showed significantly increased newborn cell proliferation in the dentate gyrus, but this was not maintained into aging. Long-term potentiation was significantly enhanced in subfield CA1 of hippocampal slices from aged 11β-HSD1(−/−) mice. These data suggest that 11β-HSD1 deficiency enhances synaptic potentiation in the aged hippocampus and this may underlie the better maintenance of learning and memory with aging, which occurs in the absence of increased neurogenesis.